АРХЕТИПИ У ТВОРЧОСТІ ВАСИЛЯ КУРИЛИКА НА ПРИКЛАДІ СЕРІЙ «ОСТАННІ ДНІ», «ПЕРШИЙ ЕМІГРАНТ» ТА «ВЕЛИКА САМОТНІСТЬ» - О., Береговська Х. (Zenodo, 2019)
The aim of this paper is to highlight one of the fundamental themes of the works of Canadian artist William Kurelek – archetypes. We know that he was very interested in the subjects of philosophy and psychology, and often wrote about them. He attempted to answer his own questions about life, loneliness, society, ego, and divinity using a theoretical/practical approach. Of the myriad of archetypes that we find in his work – the Mother, the Family, Loneliness, the Newcomer, we will focus on Loneliness. We will use the scientific method of analysis and synthesis to create a scholarly work about this topic. In general, an archetype as such contains within it symbols which reveal the nature of things, but it does not necessarily appear as a complete entity in every painting. Therefore, to understand the choice of symbols we need to imagine them in a dialogue with the observer, as the symbol exists in and of itself: it acts on each observer in the same way, regardless of the personality of the observer, and it derives its strength and longevity from the sub-conscious influence of the archetype. When observing and comprehending symbols, human consciousness is always secondary to the subconscious. Also, archetypes can work in unison, creating complementary pairs of sorts. For example, the Mother archetype can exist on its own, but at the same time it can be connected to the Child archetype. In the same way, the Loneliness archetype can be connected to the Collective archetype. Each of the archetypes in Kurelek’s works encompasses a wide range of content, and these ideas build on each other and feed off each other. If we consider an archetype as the nucleus around which ideas collect and take on physical form, it is logical that there will be many connections developing not only between the nucleus and the individual ideas, but also between the ideas themselves. This is apparent in Kurelek’s choice of subject matter in the paintings which feature many people – where we see multiple interwoven plots, fates, and lost souls. William Kurelek was a Canadian painter of Ukrainian descent. He was born on the northern Canadian prairies, in the province of Alberta, in 1927. He worked in various locales in Canada, Mexico, and Great Britain. In his 50 years, he created almost ten thousand paintings. A burning desire to explore his ethnic heritage, combined with an adolescence spent not fitting in to the local social scene created a palette populated by prejudices and psychological complexes – perhaps even phobias – which eventually became the catalysts that propelled Kurelek’s creative explorations. Such character building began when his family moved to the town of Stonewall, Manitoba in 1933. In that town, Kurelek spent his youth. This period is considered one of the most complex of his life, and it left a lasting impact. It is precisely the social and psychological events that he experienced in Stonewall which crystalized the early upbringing of the young artist, giving birth to the drive from which arose the first of his original subject matter, matter which was rich with meaning, but events which also led to the numerous transformations and growth in his work. In the early life of the “special” firstborn son of a Ukrainian immigrant farmer, we can see a series of factors which would influence his art and creativity. First, the inability of his ambitious, yet burdened by debt, father to understand – much less nurture – his son’s talent and artistic aspirations; this led to a certain insecurity in William in dealing with the everyday world around him. In addition, he suffered daily bullying at the hands of his classmates because he spoke a different language – he was a Ukrainian speaker in an English world. As a result, he developed very low self-esteem and often locked himself in his own world. The youngster aspired to discover himself in art – at first by himself, but later at the faculties of three Universities. Second, ignoring the constant nagging and comparisons to his younger brother, William wanted to prove the worth and value of his talent to his father through the art itself. Stories about Ukraine which he heard from his parish priest enthralled the young Kurelek, who became eager to explore his heritage through art, or rather to use art to conceptualize and visualize his heritage. Third, Kurelek’s constant search for himself, and later for God in himself. He attempted to find salvation and achieve spiritual purification by constantly creating art. This one factor, in fact, was the reason for a paradigm shift in his creativity – therefore, Kurelek’s work can be divided into two distinct creative periods: before and after his conversion to Christianity. The reason for his conversion was a debilitating illness – depression – for which the artist sought treatment at three separate hospitals in Great Britain. It was at those hospitals, after long discussions with the doctors, that art became an anti-depressant for him and became a de facto drug in his fight with the disease. His faith, which led him to seek strength in a higher source, was a constant source of inspiration for him throughout this period. In his work, Kurelek dealt with scores of socio-psychological topics; he posed and attempted to answer questions about thematic, conceptual, and stylistic problems which are faced by painters, combining them in one ideological platform. The artist, highly introverted, managed to combine in his work the varied choice of subject matter and stylistic naivete of Bregel with the hidden meanings of abstract painters. Results. Canadian artist William Kurelek utilised a wide arsenal of artistic archetypes in his work, and personifi ed them in his pseudo-historical series “Ukrainians in Canada”, “Poles in Canada”, “Jews in Canada”, and “People of the Arctic”, “encoding” into each ethnic group the universal concept of nationhood. Novelty. For the first time, the works of William Kurelek will be examined through the lens of archetypes. Not only for the roles that they played in his choice of themes, but also for the universal phenomena that they represent – that is to say the never-ending process of self-exploration, as well as his translation and transmission of his personal experiences and in particular, and mid-20 th century Canadian society in general